Verifikasi metode Uji Penentuan Kelemasan Kulit Tersamak Menggunakan Softness Tester - Eko Nuraini (UIN Sunan Kalijaga Yogyakarta, 2023)
Softness tester test method is used to test the softness of tanned leather samples, especially for leather that requires a certain flexibility. There needs to be standardization or verification of test methods as re-confirmation in ensuring the test method used. There is verification so that the data produced is accurate and can maintain quality control of the results of the tests. Tanned leather turns limp due to the addition of chemicals. So far, the method of testing for weakness in the physical testing laboratory has never been verified. This study aims to verify the skin elasticity analysis method, it is hoped that the results of the verification can later be used for routine testing. The skin sample used was goat skin for the jacket material. The test was determined using a Softness tester. Parameters of the analysis method used precision, accuracy and testing uncertainty. The results obtained were SD 0.099;%RSD 1.53, a precision value of ≤ 2% can be stated as good precision; accuracy value 99.37%≥95% accuracy value meets the requirements; bias value 0.629. The results of the uncertainty calibration softness 0.0085; accuracy uncertainty 0.057; the combined uncertainty value is 0.058 and the expanded uncertainty value is 0.116. The softness value of the goat skin sample for jacket material was 6.49 ± 0.116, fulfilling the standard quality requirements for jacket material according to SNI 4503:2011. The conclusion obtained by the analyst is that they are able to perform skin flexibility tests according to the SNI ISO 17235:2012 method and this method can be used in the ATK Polytechnic Physical Testing Laboratory.